The Methodology of Muʿtazilah Exegesis: Study of Ḥākim Al-Jushamī’s Al-Tahdhīb Fī Al-Tafsīr - Didik Andriawan (QOF, 2022)
This article will discuss the method used throughout al-Tahdhīb fī al-Tafsīr by Ḥākim al-Jushamī, one of the most prominent interpreters of the Muʿtazilah school. The discussion in this article will center on a variety of topics, including Ḥākim al-Jushamī biography, his works, general information on al-Tahdhīb fi al-Tafsir, systematics of interpretation, reference materials, and the methodology behind his interpretation. The objective of this article is to introduce the interpretation of al-Tahdhīb, to explore the nature and technique of Muʿtazilah’s interpretation in the Middle Ages in general and Jushamī’s interpretation in particular. This study employs a qualitative approach based on library research to focus on the major source of al-Tahdhīb fi al-Tafsīr’s as well as a variety of supplementary materials pertinent to the topic under discussion. Jushamī was a Muʿtazilah scholar who lived in the school’s final moments before its ruination. He is also a theologian of interpreters with a reputation for profound knowledge and one of Zamakhsharī’s teachers. The book of al-Tahdhīb is an Arabic commentary that discusses the entire 30 juz of the Qurʾān in 10 volumes, in the sequence of the Muṣḥaf. This commentary is one of the commentaries written by Muʿtazilah scholars that is available to us in its entirety. Jushamī described the passages of the Qurʾān based on the understanding of the Muʿtazilah school in his interpretation. The sources of interpretation in al-Tahdhīb include the narrations from the ṣaḥābah, the tabiʿūn, the tābiʿ al-tabiʿīn and scholars, especially the Muʿtazilah scholars. Among the methods of interpretation in al-Tahdhīb were the Interpretation of verse by verse, interpretation by hadith, the use of the narration of Isrāiliyāt, explanation of fiqh, kalam, and tasawuf issues, and the munāsabah method.